Socioeconomic Characteristics of Seaweed Cultivation Business in Southeast Sulawesi Province, Indonesia - Nuryadi, Ahmad Muhlis; Muthalib, Abdul Aziz; Hartati (Journal of Management Studies and Development, 2024)
The seaweed cultivation business in the fisheries sector remains the livelihood of coastal communities; thus, it must be designed based on welfare improvement, business sustainability, and regional development. The various efforts must begin with studies on the characteristics of the farmers and seaweed businesses. Therefore, this study analyzes the characteristics of seaweed cultivation businesses from socioeconomic aspects. The research was conducted in two regencies in Southeast Sulawesi Province: South Konawe Regency and Bombana Regency, as the research location's main parameters. This study employed quantitative descriptive analysis. The data was obtained through field surveys on seaweed farmers and seaweed trading business actors. This research emphasizes social aspects, including age, education, business experience, and family dependents, while the economic aspects focus on capital and marketing. The results revealed that the seaweed farmers in Southeast Sulawesi Province are mainly those of working age with relatively fewer family dependents and excellent experience but a low level of formal education. This phenomenon makes several parties, including the authorities and universities, obliged to take action to improve farmers’ quality and skills to be more agile and innovative. Moreover, Most seaweed farmers obtained capital from traders; consequently, they had to sell their harvest to traders below the market price. Therefore, developing a partnership system supporting and protecting groups of farmers, traders/cooperatives, and the seaweed agroindustry with additional capital and technological support from the government and universities is recommended.